Color Doppler Ultrasound of Carotid and Vertebral Vessels: Anatomy, Technique and Reporting - Lotfi, Mehrzad (Galen Medical Journal, 2016)
Color Doppler study of carotid and vertebral arteries is a non-invasive, reliable and also easily available, cost-effective method for screening and follows up of patients at risk of stroke to differentiate patients need surgery or intervention from whom could be followed by medical management. IÂ Â  reviewed anatomy of cervical arteries and different techniques such as B- mode or gray scale scanning, color flow mapping and spectral analysis for evaluation of both carotid and vertebral arteries.